Analisis Dampak Hilirisasi Terhadap Pertumbuhan Ekonomi Di Indonesia - Akhmadi, Fauzan (STKIP MAJENANG, 2024)
The processing and utilization of natural resources aims to meet all human needs in each country, both in the agriculture, fisheries, and mining sectors. Natural resource law focuses more on exploitation and utilization, while environmental law focuses on its preservation, indeed these two laws seem to contradict and there is a difference. But this is always related to each other and cannot be separated. Downstream which refers to the development or transformation of the added value of a product or commodity from raw materials upstream to semi-finished products or finished products downstream. In other words, through the downstream program, Indonesia has the opportunity to increase revenue by managing the production process from upstream to downstream. Downstream is the main focus of the government because downstream has significant added value potential for the country's economy. The government said the key to Indonesia's economic growth reaching 6-7% lies in downstream. One of the downstream industry programs is predicted to be an important step to support the momentum of golden Indonesia 2045.